Adición de prebiótico en la elaboración de compota de banano (Musa sapientum L) - Lara Ramos, Luis Alberto (2012)
This research has as main objective the development of a banana compote with added prebiotic as an alternative to add value to bananas is one of the main crops at national level, however, this fruit is not highly industrialized and export are mostly as whole fruit. There are few companies in the industrialization of bananas, most of these make the fruit puree is exported to different countries to use as feedstock for the production of different products, including jams. The objective of this research is to develop a banana compote adding prebiotic to obtain a functional food. Currently there is a change in working habits as a way to transform the raw material for food, so it no longer seeks only one food that will bring satisfaction to be consumed, but that contains properties and ingredients that provide an extra benefit consumer health. Why in this experiment were used: banana puree, water, prebiotic and ascorbic acid This work was done in the city of Quevedo, specifically in the dairy plant and Laboratory of Food Science, Quevedo State Technical University, located in the experimental farm at Km La Maria road 7 ½ Quevedo - El Empalme Canton entry Mocache, Province of Los Ríos. Factorial arrangement was established AxBxC, with twelve treatments and three replicates, the statistical test used was the Tukey at 5% probability. The factors studied were: A (percentage of water 10% and 20%) B (Percentage of prebiotic BENEO 5% and 10%) C (ascorbic acid Percentage 2%, 2.5% and 3%). The variables analyzed were: physical analysis (pH and ° Brix) for all treatments of the three repetitions, bromatological analysis (moisture, dry matter, ash, fat, protein, fiber, ELNN and energy) to the best treatment in three replicates and second repetition for the twelve treatments microbiological analysis (Coliforms, Total Yeasts and molds). The process for obtaining the compote was performed under the Ecuadorian Technical Standards drained and chopped food packaged for infants and young children. NTE INEN 2 009:95 During the preparation of stewed banana with added prebiotic held the respective reception and selection of raw materials, followed by obtaining the mashed banana performing the physical tests (pH and ° Brix), then weighed individually, mixed of all ingredients and additives that are part of the formulation, immediately took to the process of pasteurization, cooling, packaging, labeling and storage of the product. And finally to physical analysis (pH and ° Brix) the finished product. Once the banana compote respective samples were sent to the second repetition for conducting microbiological analysis. The results of this study permitted the identification of treatment No. 10 (Mashed banana + 20% water + 10% + 2.0% of prebiotic ascorbic acid) as the best, because that is closer in terms of technical parameters physical analysis as established by the Ecuadorian Technical Standards INEN 2 009:95. That is, the banana sauce with added prebiotic treatment 10 is 4.17 of pH and Brix 23.07 of the Rules state that above any fruit compote must have a minimum of 15% Brix and pH 4.5 maximum.